Description of the larva and pupa of Culex (Melanoconion) dureti Casal & Garcia and redescription of the adult male (Diptera: Culicidae) - Bangher, Débora N.; Almirón, Walter R.; Stein, Marina (Zootaxa, 2024)
Culex (Melanoconion) dureti Casal & García, 1968 was described based on the adult male. In this article, we describe and illustrate the pupa and the fourth-instar larva and provide a redescription of the adult male. Diagnostic characters of the male genitalia and fourth-instar larva are also provided to separate Cx. dureti from closely related species. Possible phylogenetic relationships of the immature stages of the Inhibitator Group are discussed. Information on distribution and bionomics of the species is also provided. The female remains unknown.